Career change in a small island tourism destination: evidence from former hospitality managers - Zopiatis, Anastasios; Theocharous, Antonis L. (My University, 2020)
Recent decades have revealed labor turnover to be the Achilles’ heel of the hospitality industry. This has led interested members of the academic community to investigate the topic from an array of perspectives. Managerial career change, which shares certain theoretical attributes with the phenomenon of turnover, has heretofore been inexplicably overlooked by academia, despite its strong operational and strategic implications. By espousing a qualitative methodology, namely grounded theory, this study builds on existing theoretical capital and investigates the factors contributing to managerial career change, which is defined as a manager’s voluntary decision to exit the hospitality industry and seek employment in other segments of the economy. Ten in-depth interviews with individuals who had invested in hospitality degrees, so as to take on management-level positions, but subsequently decided to pursue other careers, have provided insight on the factors contributing to such decisions. Our findings should be of interest to industry stakeholders, as they may assist in further theorizing the social process leading to managerial career change.
Keywords: Turnover; Cyprus; Grounded theory; Managerial career change